Zoology / Alfred M. Elliott, - Elliott, Alfred M.
The science of zoology, beginnings and nature, earyl history of life, units of life cells; organized animal, from single cells to many cells; relationships, the animal and its environment, orderliness; the rise of animal life, the first and animal-protozoa, sponges and the radial animals, primitive bilateral animal-flatworms, the tube-within-a tube body plan, shelled animal-mollusk; organ sytems of man, housing, support, and movement, coordination, the digestive system.